Evaluating labour market policy - Eichhorst, Werner; Konle-Seidl, Regina (Bonn, 2016)
"Labour market institutions are deemed to have a great influence on the level and structure of employment. This holds for regulation on employment protection, minimum wages or tax/benefit systems as well as active labour market policies. This is why policy makers implement labour market reforms in order to stimulate job creation. The hope linked to labour market reforms is a sustainable reduction of structural and cyclical unemployment. This chapter reviews major approaches and findings on the evaluation of the impact of different labour market institutions but pays particular attention to active labour market policies that play an important role in the portfolio of economic policy makers in many OECD countries for several decades. Rigorous evaluation in this field has grown rapidly since the early 2000s. Describing concrete evaluation studies we focus on the important role of good data, methodological problems and discuss the impact on participants as well as possible effects on non-participants. We further describe how to investigate whether a programme also achieved positive net effects at a macroeconomic level. Finally, we have a closer look on policy implications and interactions with other institutional features."